Azimova, Lala - (:unkn) unknown (My University, 2026)
Lala Hajiagha Azimova was born in Baku, Azerbaijan, in 1977 into an intellectual family. From 1994 to 1998, she studied at the Faculty of Metallurgy of Azerbaijan Technical University, where she received a Bachelor's degree in Metallurgy. From 1998 to 2000, she completed a Master's degree in Non-Ferrous and Rare Metals Metallurgy at Azerbaijan Technical University. From 2000 to 2013, she worked as a Senior Laboratory Assistant at the Department of Metallurgy and Materials Science. From 2013 to 2017, she served as an Assistant Lecturer, and since 2017, she has been working as a Senior Lecturer at the Department of Metallurgy and Materials Technology. In 2003, she was admitted as a doctoral researcher (dissertant) in the specialty of Metallurgical Technology (3315.01). She has completed her PhD dissertation in Engineering at the Department of Metallurgy and Materials Technology. She successfully passed the doctoral qualifying examinations, including the foreign language examination and the specialization examination. She is the author of approximately 51 scientific publications and methodological materials. Among them, 22 journal articles and conference papers related to her dissertation research have been published in national and international journals and conference proceedings, including five papers indexed in Scopus and other internationally recognized abstracting and indexing databases. She is currently a Senior Lecturer at the Department of Metallurgy and Materials Technology, Azerbaijan Technical University.